PHoral: Effects of carnosine supplementation on quantity/quality of oral salivae in healthy volunteer and in subjects affected by common oral pathologies. Issue 25 (25th June 2021) - Ciulla, Michele M.; Re, Dino; Gilardoni, Ettore; D'Amato, Alfonsina; Altomare, Alessandra; Baron, Giovanna; Carugo, Stefano; Aldini, Giancarlo
Abstract: Background: Diseases of the oral cavity (OC) with an infectious trigger such as caries and periodontal disease are extremely common in the general population and can also have effects at the cardiovascular level. The oral salivary flow, with its buffering capacity, is able to regulate the pH of the OC and, therefore, significantly contribute to the ecological balance of the microenvironment in which the oral microbiome (OM) develops. On the other side, when the quality/quantity of salivary flow is altered it is supposed the disruption of this balance with the potential increase in oral pathogens and triggered diseases. Among the endogenous substances able to exert a significant effect on the salivary flow and its characteristics, carnosine (Car), a dipeptide originally isolated in skeletal muscle, represents, thanks to the known buffering properties, a promising principle. Methods: We aimed this protocol to evaluate the quantitative/qualitative characteristics of the salivary flow in healthy volunteer subjects (n = 20) and in subjects suffering from common OC pathologies (n = 40), before and after 7 days of supplementation with SaliflussTM (Metis Healthcare srl, Milan, Italy), a Class I medical device on the market as 400 mg mucoadhesive oral tablets that has Car as the main ingredient. Discussion: Combining the characteristics of saliva with the OM and comparing them with OC pathologies, we expect to clarify their reciprocal relationship and, using quantitative proteomics techniques, to help clarify the mechanism of action of Car.